(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Lightweight foamed concrete (LFC) can be modified to have a reliable amount of compression protection, making it possibly to be used in low-rise building as load-bearing walls. LFC with coir fibre has experienced massive improvement in its strength compared to the normal LFC. Therefore, this particular investigation explores the contribution of coir fibre in the lightweight walling construction in terms of structural behaviour under axial compression. Fundamental steps need to be carried out to investigate thoroughly its behaviour before this innovative product can be used in practice. Coir fibre has potential to be used as replacement for the coarse aggregate in concrete to produce structural concrete. The experimental results shown that when 1400kg/m3 and 700kg/m3 density samples were associated to become one single solid concrete, the total density will be reduced and the thermal performance of the concrete will be enhanced. In this case, the panel recorded higher strength under compression than the control specimen. Due to the integrity of the reinforcing agent, the panel yielded better enhancements in the structural behaviour because natural fibres have strong resistance upon compression.Â